The Effects of Vitamin D Supplementation on Anthropometric and Biochemical Indices in Patients With Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-analysis - Rezaei, Shahla; Tabrizi, Reza; Nowrouzi-Sohrabi, Peyman; Jalali, Mohammad; Shabani-Borujeni, Mojtaba; Modaresi, Shayan; Gholamalizadeh, Maryam; Doaei, Saeid (Frontiers in Pharmacology, 2021)
Background: Vitamin D was reported to be associated with non-alcoholic fatty liver disease (NAFLD). This systematic review and meta-analysis aimed to investigate the effects of the vitamin D supplementation on anthropometric and biochemical indices in patient with NAFLD. Methods: PubMed, Web of science, Scopus, and Embase databases were explored to identify all randomized controlled trial (RCT) investigating the effects of vitamin D supplementation on anthropometric and biochemical indices in patients with NAFLD. A random-effects model was used to pool weighted mean difference (WMD) and corresponding 95% confidence intervals (CIs). The statistical heterogeneity among the studies was assessed using I2 statistic (high ≥ 50%, low < 50%) and Cochran’s Q-test. Results: Sixteen RCTs were included in this meta-analysis. The results identified that high-density lipoprotein-cholesterol (HDL-C) level significantly increased following vitamin D supplementation (P = 0.008). Vitamin D reduced body weight (P = 0.007), body mass index (P = 0.002), waist circumstance (WC) (P = 0.02), serum alanine transaminase (ALT) (P = 0.01), fasting blood sugar (FBS) (P = 0.01), homeostatic model assessment for insulin resistance (HOMA-IR) (P = 0.004), and calcium (P = 0.01). No significant changes were found on body fat, triglyceride (TG), total cholesterol, low-density lipoprotein-cholesterol (LDL-C), aspartate transaminase, alkaline phosphatase, gamma-glutamyl transferase, and adiponectin following vitamin D supplementation. Conclusions: Vitamin D had significant effects on anthropometric and biochemical indices including HDL-C, body weight, BMI, WC, serum ALT, serum FBS, HOMA-IR, and calcium. Vitamin D supplementation can be considered as an effective strategy in management of patients with NAFLD.